“Shari’ah Politics”: Halal Certification and Labeling in the Indonesian Context - Sopiyudin, U. (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2024)
Halal certification and labeling are important to ensure that products circulating on the market comply with Sharia principles. Sharia politics involving government policies, religious institutions and community organizations have a crucial role in this process. Purpose This discussion aims to analyze the political dynamics of Sharia in the context of halal certification and labeling in Indonesia. The analysis methodology used in this discussion includes a qualitative approach with document analysis. Through this approach, it is hoped that a comprehensive picture can be obtained regarding how Sharia politics influences the halal certification and labeling process in Indonesia. The implementation of halal certification and labeling in Indonesia faces many challenges from process, implementation, to impact on society. Even though there are challenges that must be faced, including costs and bureaucracy, this policy also opens up great opportunities for the development of Indonesia's halal industry, both in the domestic and international markets. Halal certification and labeling in Indonesia can still be expected to be one of the steps in the struggle for sharia politics in Indonesia.Keywords: sharia politics, certification, labeling, halal, challenges   AbstrakSertifikasi dan Labelisasi halal menjadi penting untuk memastikan bahwa produkproduk yang beredar di pasar sesuai dengan prinsip-prinsip Syariah. Politik Syariah yang melibatkan kebijakan pemerintah, lembaga keagamaan, dan organisasi masyarakat memiliki peran krusial dalam proses ini. Tujuan Pembahasan ini bertujuan untuk menganalisis dinamika politik Syariah dalam konteks sertifikasi dan labelisasi halal di Indonesia. Metodologi Analisis yang digunakan dalam pembahasan ini meliputi pendekatan kualitatif dengan analisis dokumen. Melalui pendekatan ini, diharapkan dapat diperoleh gambaran yang komprehensif mengenai bagaimana politik Syariah mempengaruhi proses sertifikasi dan labelisasi halal di Indonesia. Pelaksanaan Sertifikasi dan labelisasi halal di Indonesia, banyak berhadapan dengan tantangan dari proses, penerapan, hingga dampak untuk masyarakat. Meskipun ada tantangan yang harus dihadapi, termasuk biaya dan birokrasi, namun kebijakan ini juga membuka peluang besar bagi pengembangan industri halal Indonesia, baik di pasar domestik maupun internasional. Sertifikasi dan labelisasi halal di Indonesia tetap dapat diharapkan bisa menjadi salah satu langkah perjuangan dari politik syariah di Indonesia.Kata Kunci : politik syariah, sertifikasi, labelisasi, halal, tantangan